Expression of ALDH1 and TGFβ2 in benign and malignant breast tumors and their prognostic implications - Zheng, Rongsheng (e-Century Publishing Corporation, 2014)
The specific mechanism underlying the role of putative stem cell marker aldehyde dehydrogenase 1 (ALDH1) playing in development and progression of breast cancer is currently unclear. Transforming growth factor β (TGFβ) signaling pathway is reported to be activated in most cancers. Thus a study was initiated to explore possible differences and correlation of ALDH1 and TGFβ2 expression in the most common malignant and benign tumors of the breast in Chinese women. Samples of 75 breast cancer tissues, 30 paracancerous normal tissues, and 39 fibroadenoma breast tissues were investigated for the expression of ALDH1 and TGFβ2 using immunohistochemistry. The positive rates of ALDH1 and TGFβ2 protein were 62.67% and 66.67%, respectively, in breast cancer tissues, which were significantly higher than that in normal fibroadenoma breast (P<0.05) and paracancerous tissues (P<0.01). ALDH1 and TGFβ2 status were significantly associated with tumor histological grade and receptor status (P<0.05). Expression of ALDH1 was found to be positively correlative to TGFβ2 in breast cancer (r = 0.33, P<0.01). Expression of both proteins remained significantly associated with reduced overall survival (OS) by univariate analysis (P<0.05). Multivariate Cox regression analysis showed that ALDH1 expression, tumor stage, and lymph node status are independent prognostic factors in invasive breast cancer patients. Thus ALDH1 and TGFβ2 play important roles in the development of breast cancer. The ALDH1 phenotype is an independent predictor of poor prognosis, and TGFβ2 signaling pathway activation might be involved in the pathological regulation of ALDH1 in breast cancer.